PENGEMBANGAN INSTRUMEN TES KOGNITIF BERDASARKAN TAKSONOMI BLOOMANDERSON PADA MATERI ELASTISITASDAN HUKUM HOOKE DI SMA PEKANBARU - Yunita Ayana; Fakhruddin Z; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This study aims to produce a cognitive test instrument based on Bloom Anderson's taxonomy on material elasticity and Hooke's law to measure students' cognitive abilities. This type of research used in research is Research and Development (R&D) by using a 4-D development model (Define, Design, Development and Dissemination). The research phase starts from defining and defining the development requirements, then continues the design phase by developing question indicators based on Bloom Anderson's taxonomy. The test questions developed were in the form of multiple choice consisting of 6 cognitive levels (C1-C6) totaling 18 items based on Bloom Anderson's taxonomy. After being developed, it was continued with question validation by 3 lecturers of Physics Education FKIP Riau University and 3 Physics teachers. The valid questions were limited to 36 students. The results of the analysis of the validation of the test instrument by the expert team showed that the cognitive test was categorized as very valid with a value of 80.5%. Based on a limited trial, it was found that the validity of the items from 18 questions was stated as 15 valid questions, and had a reliability value of 0.61 with a high level of reliability. So that the developed test instrument is used to measure students' cognitive abilities on material elasticity and Hooke's law.Keywords:development, test instruments, Bloom Anderson taxonomy, elasticity and Hooke's law